2018
DOI: 10.3892/ol.2018.9508
|View full text |Cite
|
Sign up to set email alerts
|

Identification of core genes and prediction of miRNAs associated with osteoporosis using a bioinformatics approach

Abstract: Osteoporosis (OP) is an age-related disease, and osteoporotic fracture is one of the major causes of disability and mortality in elderly patients (>70 years old). As the pathogenesis and molecular mechanism of OP remain unclear, the identification of disease biomarkers is important for guiding research and providing therapeutic targets. In the present study, core genes and microRNAs (miRNAs) associated with OP were identified. Differentially expressed genes (DEGs) between human mesenchymal stem cell specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…576 genes were detected as the target of this miRNA and KEGG pathway analysis has shown that these genes were mostly enriched in adrenergic signaling in cardiomyocytes and adherens junction. Some other reports in the literature that show the association of these two pathways with osteoporosis [54,55]. Furthermore, target genes of miR-133a-3p were used to establish the PPI network by using Cytoscape and six genes in the PPI network were identified as hub genes (degree≥15).…”
Section: Discussionmentioning
confidence: 99%
“…576 genes were detected as the target of this miRNA and KEGG pathway analysis has shown that these genes were mostly enriched in adrenergic signaling in cardiomyocytes and adherens junction. Some other reports in the literature that show the association of these two pathways with osteoporosis [54,55]. Furthermore, target genes of miR-133a-3p were used to establish the PPI network by using Cytoscape and six genes in the PPI network were identified as hub genes (degree≥15).…”
Section: Discussionmentioning
confidence: 99%
“…A microRNA profiling microarray expression dataset consisting of three pairs of parental EOC cells and their PTX-resistant sublines (GSE148251) ( 20 ) was downloaded from Gene Expression Omnibus (GEO platform). The miRNA expression levels were analyzed using GEO2R bioconductor project and provided as log2 ratios ( 21 ). We explored three mRNA target-predicting algorithms including mirSVR, Target scan and miRDB to screen the potential downstream targets of hsa-miR-105 ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Microarray analysis, as an important tool in the field of tumor medicine, has important clinical application value in the key genes, molecular diagnosis of some diseases, molecular diagnosis, and the discovery of new drug targets. [ 2 , 3 ] There are already many disease databases, such as gene expression omnibus (GEO) [ 4 ] and the cancer genome atlas. Also, more and more researchers are using bioinformatics analysis.…”
Section: Introductionmentioning
confidence: 99%